Effects of Dietary Salt Intake on Renal Function: A 2‐Year Study in Healthy Aged Cats. (3rd April 2013) - Reynolds, B.S.; Chetboul, V.; Nguyen, P.; Testault, I.; Concordet, D.V.; Carlos Sampedrano, C.; Elliott, J.; Trehiou‐Sechi, E.; Abadie, J.; Biourge, V.; Lefebvre, H.P.
<x xml:space="preserve">Abstract</x> Background Increasing salt intake to promote diuresis has been suggested in the management of feline lower urinary tract disease. However, high dietary salt intake might adversely affect blood pressure and renal function. Objectives The objective of this study was to assess the long‐term effects of increased salt intake on renal function in healthy aged cats. Methods This study was controlled, randomized, and blinded. Twenty healthy neutered cats (10.1 ± 2.4 years) were randomly allocated into 2 matched groups. One group was fed a high salt diet (3.1 g/Mcal sodium, 5.5 g/Mcal chloride) and the other a control diet of same composition except for salt content (1.0 g/Mcal sodium, 2.2 g/Mcal chloride). Clinical examination, glomerular filtration rate, blood pressure measurement, cardiac and kidney ultrasonography, and urinary and blood tests were performed before and over 24 months after diet implementation. Statistics were performed using a general linear model. Results Sixteen cats completed the 2 year study. The only variables affected by dietary salt intake were plasma aldosterone and urinary sodium/creatinine ratio, respectively, higher and lower in the control group all over the study period and urinary specific gravity, lower in the high salt diet group at 3 months. Conclusions and Clinical Importance Glomerular filtration rate (GFR), blood pressure, and other routine clinical pathological variables in healthy aged cats were not affected by dietary salt content. The results of this 2 year study do not support the suggestion that chronic increases in dietary salt intake are harmful to renal function in older cats.